Estimates of genetic variances and interrelationships of traits associated with Striga resistance in maize - Akanvou, L.; Doku, E.V.; Kling, J. (1997)
The choice of the selection method to be used in the genetic improvement of a crop depends upon the type of gene action controlling the characters under study. Design 1 crosses were made in an open-pollinated maize population, TZL Composite-1 C1. As a result, 320 full-sib families were generated and tested under artificial infestation of Striga at two locations, Mokwa and Abuja in Nigeria. Study of gene action involved in the inheritance of S. hermonthica resistance was done. Additive genetic variance was a major portion of the genotypic variance for characters like ear Striga rating (sigma 2a = 0.41+/-0.15 and sigma 2d = -0.20+/- 0.23), yield of infested plants (sigma 2a = 401564+/-172649 and sigma 2d = 57127+/-315131) and for the Striga syndrome rating (sigma 2a = 0.28+/-0.12 and sigma 2d = 0.03+/-0.21). However, the number of Striga plants supported by the host was controlled by non-additive gene action (sigma 2a = 75.69+/-76.64 and sigma 2d = 211.47+/-134.48). Grain yield was positively correlated to the number of ears harvested (rg = 0.99+/-1.12), but negatively correlated to Striga syndrome rating at 8 weeks after planting (rg = -0.92+/-0.93), ear Striga rating at harvest (rg = -0.88+/-1.28), and to a lesser extent, to Striga counts at 8 weeks (rg = -0.22+/-0.46) and at 10 weeks (rg = -0.09+/-0.75) after planting.